Are Trichoderma atroviride and Trichoderma harzianum Effective to Control Fusarium Associated With Tomato Wilt? - WILFRIDUS ADYATMA PUTRANTO; RULLY ADI NUGROHO; PETRUS SUNU HARDIYANTA; DESTI CHRISTIAN CAHYANINGRUM (Indonesian Society for microbiology, 2021)
The pathogenic fungi, such as Fusarium in the rhizosphere of tomato (Solanum lycopersicum) negatively affects the yield and quality of the plant. A number of biological control agents have been used for protecting tomato plants against wilt diseases including various fungal species. The objective of this study was to evaluate the antagonism effects of Trichoderma atroviride and T. harzianum against the pathogen Fusarium sp. associated with tomato wilt. In this study, the antagonism of these Trichoderma spp. against the Fusarium sp. was tested in vitro by the dual culture technique, and the percentage inhibition of radial growth (PIRG) and the antagonism reaction (scale 1-5) were evaluated. The results showed that T. atroviride and T. harzianum led to 70.8% PIRG and scale 1 antagonism reaction, and 40.6% PIRG and scale 3 antagonism reaction against Fusarium sp. associated with tomato wilt after 7 days of incubation, respectively. These results indicate that application of T. atroviride and T. harzianum may be promising approach for biological control of Fusarium wilt of tomato and may play an important role in sustainable agriculture.